2014
DOI: 10.1136/annrheumdis-2014-eular.2435
|View full text |Cite
|
Sign up to set email alerts
|

AB0689 Association between MRI Inflammation and Bone Loss in Early Axial Spondyloarthritis

Abstract: Background The association between MRI inflammation and bone loss in early axial spondyloarthritis (axSpA) patients is not sufficiently studied. Objectives Establishing the association between MRI inflammation of sacroiliac joints (SIJs), lumbar spine (LS) and hip joints (HJs) and bone loss in the nearby bone-joint system in early axial axSpA patients. Methods 73 patients (33 men and 40 women) with early axSpa were examined: mean disease duration 19.9±14.4 months. Patients fulfilled ASAS criteria. Mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This finding supported the Danish Health Registries’ findings that patients with AS had an increased risk of clinical vertebral and non-vertebral fractures, with the highest risk occurring within the first 2.5 years after diagnosis 38 . In addition, previous studies demonstrated that a decrease in LS-BMD was associated with active inflammatory lesions at the lumbar spine and sacroiliac joints in early AS patients 39 , 40 , and the 2-year follow-up of the DESIR cohort also showed that the prevalence of low BMD at the lumbar spine was 22.4% in patients with early axSpA 41 . Patients with a briefer disease duration may experience more severe symptoms and disease progression, leading them to seek medical attention at an earlier stage.…”
Section: Discussionmentioning
confidence: 79%
“…This finding supported the Danish Health Registries’ findings that patients with AS had an increased risk of clinical vertebral and non-vertebral fractures, with the highest risk occurring within the first 2.5 years after diagnosis 38 . In addition, previous studies demonstrated that a decrease in LS-BMD was associated with active inflammatory lesions at the lumbar spine and sacroiliac joints in early AS patients 39 , 40 , and the 2-year follow-up of the DESIR cohort also showed that the prevalence of low BMD at the lumbar spine was 22.4% in patients with early axSpA 41 . Patients with a briefer disease duration may experience more severe symptoms and disease progression, leading them to seek medical attention at an earlier stage.…”
Section: Discussionmentioning
confidence: 79%
“…This nding supported the Danish Health Registries' ndings that patients with AS had an increased risk of clinical vertebral and non-vertebral fractures, with the highest risk occurring within the rst 2.5 years after diagnosis (38). In addition, previous studies demonstrated that a decrease in LS-BMD was associated with active in ammatory lesions at the lumbar spine and sacroiliac joints in early AS patients (39,40), and the 2-year follow-up of the DESIR cohort also showed that the prevalence of low BMD at the lumbar spine was 22.4% in patients with early ax-SpA (41). As a result, appropriate bone health assessment should be performed as part of an initial treatment plan in ax-SpA patients.…”
Section: Discussionmentioning
confidence: 94%